Bernard Tschumi Draws Architecture! - Gevork Hartoonian (Footprint)
Bernard Tschumi’s delineation prepared for the Museu de Arte Contemporânea provides the starting point for this essay, which discusses the historicity of drawing and highlights the horizontality and the verticality that structure architecture’s contrast with the pictorial realm. Juxtaposing a freehand sketch with the digital image of the same project, Tschumi moves to address the paradox concerning the position of the body and drawing. This drawing also speaks for the reversal in the position of the body brought about by digital reproductivity.